The Influence Of The Level Of Cash Turnover, Accounts Receivable And Inventory On Economic Profitability At Kpri Obor Bima - JAINUDDIN STIE; Aris Munandar (Economy Deposit Journal (E-DJ), 2020)
Profitability is closely related to the use of capital in everyday business entities or cooperatives. Capital problems are the main problems that will support the operational activities of KPRI Torch Bimad in order to achieve maximum goals. Cooperative profitability can be measured by the level of cash turnover, accounts receivable and inventory. This study aims to analyze the influence of the level of cash turnover, accounts receivable turnover and inventory turnover on economic profitability in KPRI Torch Bima,. This type of research is associative research, the population used in this study is the balance sheet financial statement data consisting of principal savings data, mandatory savings and income loss consists of for 36 years from 1984 to 2019 KPRI Obor Bima. Sampling is done by purposive sampling method. Research samples taken for 7 considerations taken 7 years is because 1) the data is very updated 2) the variables in which the data are available 3) It is difficult to get an annual financial report 4) data from the year before the data are not available completely, the data processing is tested statistically through classical assumptions, multiple regression analysis, multiple correlation, determination test and hypothesis test with the T Test, F Test. The results of the research prove that partially or simultaneously cash turnover rates, accounts receivable turnover rates and rates inventory turnover has no significant and simultaneous effect on economic profitability on the KPRI Obor Bima. Keywords: , accounts receivable turnover, inventory turnover, economic profitability